Impact of diabetes mellitus on periprocedural and 18-month clinical outcomes in Korean patients requiring rotational atherectomy: results from the ROCK Registry - Su Nam Lee; Donggyu Moon; Sung-Ho Her; Won Young Jang; Keon-Woong Moon; Ki-Dong Yoo; Kyusup Lee; Jae Hwan Lee; Jang Hoon Lee; Sang Rok Lee; Seung-Whan Lee; Kyeong Ho Yun; et al. (Annals of Saudi Medicine, 2022)
BACKGROUND: Diabetes mellitus (diabetes) increases the risk of severe coronary artery calcification, which increases the complexity of percutaneous coronary intervention requiring rotational atherectomy (RA) by interfering with lesion preparation, and limiting final stent expansion. OBJECTIVE: Investigate 30-day and 18-month clinical outcomes in patients with and without diabetes treated with percutaneous coronary intervention requiring RA. DESIGN: Medical record review SETTING: Multicenter registry in South Korea PATIENTS AND METHODS: The ROtational atherectomy in Calcified lesions in Korea (ROCK) registry was a large, retrospective, multicenter study to assess RA treatment of severe coronary artery calcification. MAIN OUTCOME MEASURES: The primary endpoint was target-vessel failure including cardiac death, target-vessel myocardial infarction, and target-vessel revascularization. SAMPLE SIZE: 540 patients followed for a median of 16.1 months. RESULTS: Of the 540 patients, 305 had diabetes (56.5%). The diabetes group had a significantly higher frequency of multivessel disease; comorbidities such as hypertension, dyslipidemia, and chronic kidney disease; and lower ejection fraction of the left ventricle compared to the non-diabetes group (n=235). There were no significant differences in procedure success and complications observed between the two groups. Target vessel failure at 30 days between the diabetes and non-diabetes groups was not statistically significant in a multivariate Cox regression analysis (1.6% vs. 2.6%, adjusted hazard ratio [HR] 0.595, 95% confidence interval [CI] 0.154-2.300, P=.451). During an 18-month follow-up, the risk of target vessel failure was higher (12.5% vs. 8.9%) but the difference was not statistically significant (adjusted HR 1.393, 95% CI 0.782-2.482, P=.260). CONCLUSIONS: Patients with diabetes have a risk of complications comparable to patients without diabetes, and 30-day and 18-month clinical outcomes are similar in severe coronary artery calcification requiring RA, despite having more comorbidities. LIMITATIONS: Retrospective design. Sample size not based on power calculation. CONFLICT OF INTEREST: None.